Digital Transformation in Public Service: A Case Study of SIPRAJA Innovation in Sidoarjo: Transformasi Digital dalam Pelayanan Publik: Studi Kasus Inovasi SIPRAJA di Sidoarjo - Susanta, Rahmadhani Rizky; Choiriyah, Ilmi Usrotin (Indonesian Journal of Innovation Studies, 2023)
This research investigates the digital innovation of the Sidoarjo Public Service System (SIPRAJA) through a qualitative descriptive methodology, employing data collection techniques such as observation, interviews, and recordkeeping, utilizing both primary and secondary data. The findings reveal that the community has effectively embraced the SIPRAJA application and website, marking SIPRAJA as a noteworthy digital public service innovation. The study aligns with Rogers’ innovation characteristics, highlighting SIPRAJA’s relative advantage, compatibility with community needs, low user complexity, smooth trialability despite minor technical disruptions, and observable positive outcomes. Despite challenges, the 24-hour service provision and established performance measurement mechanisms for operators underscore the successful implementation of the SIPRAJA innovation, showcasing its potential impact on global public service advancements. Highlights: User Adoption: The study underscores the community’s seamless adoption of the SIPRAJA application, showcasing its relative advantage and compatibility with user needs. Operational Performance: Despite minor technical challenges, the 24-hour service provision and established performance measurement mechanisms highlight the successful implementation and observability of SIPRAJA’s impact on public service operations. Global Relevance: The research suggests the potential for SIPRAJA’s digital innovation to contribute to global advancements in public service, emphasizing its applicability beyond local boundaries. Keywords: Digital Innovation, Public Service, SIPRAJA, Qualitative Research, Community Adoption